2021
DOI: 10.1111/acel.13352
|View full text |Cite
|
Sign up to set email alerts
|

Short and dysfunctional telomeres protect from allergen‐induced airway inflammation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Noteworthy, treatment with the vehicle of NVP (DMSO) did not induce inflammation in lungs of inbred C57BL/6J mice ( Figure S2 ). In accordance, several drugs were previously reported to be dissolved in up to 5% DMSO for their use in preclinical mouse models [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 90%
“…Noteworthy, treatment with the vehicle of NVP (DMSO) did not induce inflammation in lungs of inbred C57BL/6J mice ( Figure S2 ). In accordance, several drugs were previously reported to be dissolved in up to 5% DMSO for their use in preclinical mouse models [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 90%
“…Conversely, in allergic diseases, the presence of shortened telomeres appears to induce airway inflammation; a positive correlation between leukocytes with shortened telomeres and inflammation in patients with severe asthma has been reported [ 100 ]. Piñeiro-Hermida et al [ 101 ] found that mice with increased TS rates due to genetic deficiencies ( G3 Tert −/− mice) or induced by 6-thio-2′-deoxyguanosine administration exhibited eosinophilia and low circulating IgE levels and that TS affects the differentiation of club cells, which are essential for eliminating harmful substances inhaled into the lungs. Tung et al [ 102 ] proposed that snoring accelerates TS in atopic patients, primarily in those with asthma and allergic rhinitis; however, a limitation of this study was that it did not identify which immune cell population is more sensitive to increased TS.…”
Section: Influence Of Immune Cells With Shorter Telomeres On Development Of Lung Diseasesmentioning
confidence: 99%
“…Another observation of interest is the shortening of telomere length in peripheral leukocytes of asthmatics ( 223 , 224 ), suggesting extensive leukocyte proliferation and found to correlate with eotaxin 1 expression ( 225 ). However, telomerase-deficient mice showed debilitating eosinophil responses in the lung and reduced eosinopoiesis, although eosinophil-independent effects of telomerase cannot be excluded ( 226 ). Whether constant eosinopoiesis in long-term severe asthmatics induces inflammaging phenotypes in eosinophils remains unknown.…”
Section: Phases Of Allergic Lung Inflammationmentioning
confidence: 99%